Prosthetic Rehabilitation of a patient with partially amputated index finger - S. Agarwal; A. Chopra; R. Mittal; M. Sethi; S. Tripathi (Nigerian Dental Journal)
Hands are capable of a wide variety of functions like touching, grasping, feeling, holding, manipulating, caressing, and more. It is a vital and important part of a person's identity and well being. Loss of part of the hands can affect esthetics; functions are undermined depending upon the severity of loss and it causes a great psychological disturbance. The prosthetic rehabilitation of a partially amputated finger presents a challenge to the Prosthodontist. This case report illustrates the procedure of fabrication of finger prosthesis using room temperature vulcanizing (RTV) silicone and intrinsic staining with modern prosthetic design to improve the esthetics of a patient with partially amputated left index finger.